A NOTE ON THE PLANKTON OF A FRESHWATER IMPOUNDMENT IN KARNATAKA - Rao, D S Krishna (Indian Journal of Fisheries, 2011)
The quiilitiitivc and quantitative composition of plankton in the Ivarukandapuiatank. Bangalore District, during the period January 1981 throughJanuary 1982, are discussed in relation to physico-chemical parameters. Phytoplanktonwas in sparss density with the number ranging from nil to 6000|mand qualitatively poor. Zooplankton was predominant throughout the year withthe number fluctuating between 21,000 and 3,50,bOO|m^, exhibiting bimodality,with a primary peak in February and a secondary one in August. The low productionof plankton as a whole was due to turbidity of waters and low nutrientof both soil and water